Electronic control of ultrafast field emission in carbon nanotube gaps - Son, B. H.; Park, D. J.; Ahn, Y. H. (Applied Physics Letters, 2019)
The electronic control of an ultrafast tunneling electron emission was demonstrated in the nanogap of a single-walled nanotube (SWNT) when irradiated by a femtosecond laser pulse. The SWNT apex possesses a nanoscale morphology with a large damage threshold and thus enabled the achievement of a large emission rate. More importantly, the DC field-emission characteristics varied when the gate bias was changed. This was analyzed in terms of the change in the effective barrier height and enhancement factors. Photoinduced electron emission was observed when the gap area was illuminated with a femtosecond laser centered at a wavelength of 800 nm. As the laser power was increased, a saturated tunneling current was observed, reaching more than 10 electrons per pulse. Finally, the photoelectron emission yield was tuned with the help of gate-induced variations in the electronic band structures of the SWNTs.
Keywords: Effective barrier heights; Electronic band structure; Electronic controls; Enhancement factor; Nanoscale morphology; Photo-electron emission; Photoinduced electrons; Single-walled nanotube